1990
DOI: 10.1021/bi00488a038
|View full text |Cite
|
Sign up to set email alerts
|

Color regulation in the archaebacterial phototaxis receptor phoborhodopsin (sensory rhodopsin II)

Abstract: Phoborhodopsin, a repellent phototaxis receptor in Halobacterium halobium, exhibits vibrational fine structure, a feature that has not been identified for any other rhodopsin pigment at physiological temperatures. This conclusion follows form analysis of the absorption properties of the pigment in H. halobium membranes containing native retinal and an array of retinal analogues. The absorption spectrum of the native pigment has a maximum at 487 nm with a pronounced shoulder at 460 nm; however, the bandwidth is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 75 publications
6
112
0
Order By: Relevance
“…Acid induces a shift of 46 nm (Fig. 1), a larger shift than the 20 nm seen in GPR (5) and a loss of vibrational fine structure in the spectrum as observed for sensory rhodopsin II (19). The GPR spectral transition fits well to a single pK a of 7.2 ( Fig 2A); however, a second component is evident in the BPR titration according to hyperbolic fits to the data that yields a diprotic fit with pK a values 6.2 and 7.8 (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Acid induces a shift of 46 nm (Fig. 1), a larger shift than the 20 nm seen in GPR (5) and a loss of vibrational fine structure in the spectrum as observed for sensory rhodopsin II (19). The GPR spectral transition fits well to a single pK a of 7.2 ( Fig 2A); however, a second component is evident in the BPR titration according to hyperbolic fits to the data that yields a diprotic fit with pK a values 6.2 and 7.8 (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…From these data, it was suggested that the size of the amino acid might be involved in determining the color of the chromophore. Whether this assumption is connected to the hypsochromic shift and the fine structure of the absorption band of SR-Il and whether it can be reconciled with current models (15,33) (36,37), which are characterized by a deprotonated Schiff base. Whereas in SR-I only an environmental change of Asp-76 is observed (37), the photoactivation of pSR-II clearly leads to a protonation of a carboxylate group, most probably Asp-75 (36).…”
Section: A)(i W)agr(r D)ag(g S) the Parentheses Denote Po-mentioning
confidence: 95%
“…Although a partial purification was accomplished (12), information was mostly restricted to spectroscopic data and physiological properties (13,14). The absorption maximum occurs at 490 nm with a shoulder at 460 nm, suggesting a planar structure of the retinal chromophore (15). Its molecular mass of 24 kDa is typical for the bacterial rhodopsins.…”
mentioning
confidence: 99%
“…7A, dashed line). Both spectra lacked obvious vibrational fine structure, characteristic of the other relatively blue-shifted microbial rhodopsins CrChR2 (54,55) and haloarchaeal sensory rhodopsin II (56).…”
Section: Namentioning
confidence: 99%